Innovations in Computer Science and Engineering Proceedings of the Third ICICSE, 2015 - Saini, H. S.; Sayal, Rishi; Rawat, Sandeep; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
The book is a collection of high-quality peer-reviewed research papers presented at the third International Conference on Innovations in Computer Science and Engineering (ICICSE 2015) held at Guru Nanak Institutions, Hyderabad, India during 7 - 8 August 2015. The book discusses a wide variety of industrial, engineering and scientific applications of the emerging techniques. Researchers from academic and industry present their original work and exchange ideas, information, techniques and applications in the field of Communication, Computing, and Data Science and Analytics.
Chapter 1. Secure ATM Door Locking System Using RFID -- Chapter 2. Analysis of Various Parameters for Link Adaptation in Wireless Transmission -- Chapter 3. N-Gram Classifier System to Filter Spam Messages from OSN User Wall -- Chapter 4. A Recent Study of Emerging Tools and Technologies Boosting Big Data Analytics -- Chapter 5. Registration Plate Recognition Using Dynamic Image Processing and Genetic Algorithm -- Chapter 6. Comparing the Capacity, NCC and Fidelity of Various Quantization Intervals on DWT -- Chapter 7. Enhancing Cloud Computing Server to Use Cloud Safely and to Produce Infrastructure of High Performance Computing -- Chapter 8. 3D Array Pattern Distortion Analysis -- Chapter 9. Elastic Search and Carrot2 Based Log Analytics and Management -- Chapter 10. High Security Pipelined Elastic Substitution Box with Embedded Permutation Facility -- Chapter 11. An Integrated Approach to High Dimensional Data Clustering -- Chapter 12. Performance Analysis of Network Virtualization in Cloud Computing Infrastructures on OpenStack -- Chapter 13. A Shoulder Surfing Resistant Graphical Password Authentication Scheme -- Chapter 14. A Proposal for Searching Desktop Data -- Chapter 15. Low Power Analog Bus for System on Chip Communication -- Chapter 16. Text Clustering and Text Summarization on the Use of Side Information -- Chapter 17. Image Correspondence Using Affine SIFT Flow -- Chapter 18. Link Quality Based Multi-hop Relay Protocol For WiMedia Medium Access Control -- Chapter 19. Assessment of Reusability Levels on Domain Specific Components Using Heuristic Function -- Chapter 20. Reliable Propagation of Real Time Traffic Conditions in VANETS to Evade Broadcast Storm -- Chapter 21. Hybrid Multi-objective Optimization Approach for Neural Network Classification using Local Search -- Chapter 22. Effectiveness of Email Address Obfuscation on Internet -- Chapter 23. A Proof-of-Concept Model for Vehicular Cloud Computing Using OMNet++ and SUMo -- Chapter 24. Password Reuse Behavior: How Massive Online Data Breaches Impacts Personal Data in Web -- Chapter 25. Identifying Significant Features to Improve Crowd Funded Projects' Success -- Chapter 26. A Survey on Challenges in Software Development during the Adoption of Agile Environment -- Chapter 27. A Novel Approach for Detection of Motion Vector-Based Video Steganography by AoSO Motion Vector Value -- Chapter 28. Image Resolution Enhancement Technique Using Lifting Wavelet and Discrete Wavelet Transforms -- Chapter 29. A Real Time Implementation of Face and Eye Tracking on OMAP Processor -- Chapter 30. A Study on Cyber Security, its Issues and Cyber Crime Rates in India -- Chapter 31. A Concept Based Model for Query Management in Service Desks -- Chapter 32. Designing Chaotic Chirikov Map Based Secure Hash Function -- Chapter 33. Data Fusion Approach for Enhanced Anomaly detection -- Chapter 34. NUNI (New User and New Item) Problem for SRSs Using Content Aware Multimedia based Approach -- Chapter 35. Computerized Evaluation of Subjective Answers Using Hybrid Technique -- Chapter 36. A Proposal: High Throughput Robust Architecture for Log Analysis and Data Stream Mining. .
Keywords: Telecommunication; Artificial intelligence -- Data processing; Numerical analysis; Communications Engineering, Networks; Data Science; Numerical Analysis